Relevance of "Pananaroon" to Islam and Culture of Meranaw - Arsalan Diamaoden; Insah Mama; Mohammad Jihan Macarambon; Marwah Camama (Philippine Association of Institutions for Research, Inc., 2020)
Meranaws of Lanao areas is known as a Riyayatan ko Kambilangataw (role model in characters and good deeds). They have their unique cultural beliefs, tradition, and ethics, such as kambilangataw (etiquette), kaseselai (giving worth), kapoporowai (praise) kasangila (heed), kapamagawida (helping each other), kapakiroroyoden (sense of empathy), and kapamagipata, (caring person). This paper attempted to describe the significance of pananaroon (Meranaw proverbs) in contemporary Meranaw society. This also to determine the role of pananaroon in the lives of the Meranaw people since time immemorial until now. Finally, this is to find out the awareness of the Meranaws regarding the practice of pananaroon from the Islamic perspective. The researchers used a qualitative-naturalistic research design. This study gathers data through an oral interview of some informants from Marawi City and Municipality of Butig, Lanao del Sur. Field-based research was undertaken through the observational method, Focus Group Discussion (FGD) with the traditional leaders, local officials, and selected respondents from the academe. Findings revealed that the etymology of the word "pananaroon" comes from the word "taro," which means speech. Pananaroon (Meranaw proverbs) is already a part of the Meranaw cultural practices, especially during important events such as a wedding, enthronement, etiquette, and settling family feuds or conflicts. The practice of pananaroon is not only confined to its relevance to the M?ranaw culture, but it also symbolizes nobility and societal rank in society.